Etika Media Sosial dalam Al-Qur’an Qs. Al-Hujurat Surat Ke-49 Ayat 6-12 “Studi Analisis Terhadap Tafsir Ijtima’i Perspektif Etika Islam Hamzah Ya’qub” - Marhalim Marhalim (KOLONI, 2026)
This study is entitled “Social Media Ethics in the Qur'an Surah Al-Hujurat Verses 6–12 (An Analytical Study of Social Interpretation from the Perspective of Hamzah Ya'qub's Islamic Ethics)”, examines Hamzah Ya'qub’s ethical thought in relation to Qur’anic social ethics. The study aims to describe the concept of social ethics in Surah Al-Hujurat verses 6–12 through the tafsir ijtima’i approach and to analyze the relevance of these values in contemporary social media practices. The ethical teachings contained in these verses are highly relevant to communication issues in today’s digital environment. This research employs a qualitative method using a library research approach. Primary data are from the Qur’an and Hamzah Ya'qub’s Islamic Ethics, while secondary data are obtained from relevant supporting literature unlike previous studies, this research seeks to formulate a Qur’anic model of social media ethics applicable to contemporary digital spaces. The findings indicate that Surah Al-Hujurat verses 6–12 provide a comprehensive framework of social ethics emphasizing communication responsibility. The main values identified include tabayyun (information verification), ishlah (conflict resolution), respect for human dignity through the prohibition of ridicule and insult, avoidance of negative assumptions (su’udzan), prohibition of tajassus (privacy invasion), and prohibition of ghibah (backbiting). From Hamzah Ya'qub’s Islamic Ethics perspective, social media practices should be guided by moral responsibility, rational ethical judgment, social benefit, and respect for others. Accordingly, Qur’anic social media ethics can be developed through five principles: information verification, communication responsibility, constructive conflict resolution, protection of human dignity, and respect for privacy.